Been a heavy life: stories of violent men - Presser, Lois (Critical perspectives in criminology, 2008)
Self and story -- Offender identities, offender narratives -- Thinking about research effects -- Research methods when research is being researched -- Reform narratives : return of the good self -- Stability narratives : never a bad self -- Elastic narratives : creative integration -- Tales of heroic struggle -- The situated construction of narratives -- The power of stories